THE ANALYSIS OF INTERNAL CONTROL SYSTEM OF CREDIT AT PT BANK SULUT TBK CENTRAL OFFICE MANADO - Gagola, Jayanti; Ilat, Ventje; Afandi, Dhullo (Universitas Sam Ratulangi, 2015)
Banks are very important in sustaining the strength andÂ fluency of the payment system and the effectiveness of monetary policy. Moreover, the bank is also the financial institutions most urgently needed in economic development. Credit in order to accelerate economic development largely channeled by banks. As a financial institution, the largest asset owned by banks are financial assets. Therefore, internal control is very important in suppressing/assessing the risks that would arise, as well as protecting the companyâ€™s assets to achieve organizational goals. The purpose of this study was to analyze the internal control systems of credit at PT. Bank Sulut Tbk Office Manado. The method used is descriptive qualitative analysis method, in which the research was carried out by comparing the existing internal control system in the Banks of the theory is based on five elements of internal control comprising: control environment, risk assessment, control procedures, information and communications and surveillance. The results shows that credit control system at PT Bank Sulut Tbk Office Manado has been good. Suggestions submitted that the management of PT Bank Sulut Office Manado should maintain the stability of credit based on the internal control mechanisms that have been implemented at this time. Keywords: internal control, credit, bank